Hubungan Keharmonisan Keluarga Dengan Prestasi Belajar Siswa Kelas X SMK Kristen 1 Tomohon - Indry Isabella Seko; Jasin Taher; Ariantje J.A. Sundah (Peneliti.net, 2023)
Family harmony is related to student achievement. A harmonious parent-child relationship will determine the child's ability to learn. A student who feels his family is harmonious will perceive their home as a happy place because the fewer problems in his family, the fewer problems the student faces. This will create a conducive atmosphere for the student's learning process so as to help in achieving the expected achievements. The study aims to determine the relationship between family harmony and student achievement. The research data was analyzed with a simple correlation technique, and the results of the data analysis found the price r XY calculate 0.474. Compared to the r XY value of table dk 30 at the significance level of 95% is 0.361, it turns out that the calculated r XY value is greater than the r XY value of the table or 0.474 > 0.361. From these results it means that there is a significant relationship between family harmony and student learning achievement. Thus the results of this test support the proposed Ha hypothesis so that it can be accepted, otherwise Ho's hypothesis is rejected. The determination of family harmony variables on the learning achievement of grade X students of SMK Kristen 1 Tomohon was 22%, while the remaining 78% was influenced by other factors that were not studied